Problem of method / by Jean Paul Sarte;translated from the French by Hazel E.Barmes - "Sarte, Jean-Paul" (London, 1960)
This book ' Problem of Method is the first part of Sartre's new theory of man as a social and political animal. It explain the theory of avowedly Marxist in a very original sense.This theory is debilitated by its rigid attachment to nineteenth- century notions of materlisim and determinism.
Keywords: Psychology